The DEAD-Box RNA Helicases of Bacillus subtilis as a Model to Evaluate Genetic Compensation Among Duplicate Genes - José Antonio González-Gutiérrez (Frontiers in Microbiology, 2018)
The presence of duplicated genes in organisms is well documented. There is increasing interest in understanding how these genes subfunctionalize and whether functional overlap can explain the fact that some of these genes are dispensable. Bacillus subtilis possesses four DEAD-box RNA helicases (DBRH) genes, cshA, cshB, deaD/yxiN, and yfmL that make a good case to study to what extent they can complement each other despite their subfunctionalization. They possess the highly conserved N-terminal catalytic domain core common to RNA helicases, but different carboxy-terminal ends. All four genes have been shown to have independent functions although all participate in rRNA assembly. None of the B. subtilis DBRH is essential for growth at 37°C, and all single deletion mutants exhibit defective growth at 18°C except for ΔdeaD/yxiN. Evaluation of double mutants did not reveal negative epistasis, suggesting that they do not have overlapping functions. The absence of any one gene distorts the expression pattern of the others, but not in a specific pattern suggestive of compensation. Overexpression of these paralogous genes in the different mutant backgrounds did not result in cross-complementation, further confirming their lack of buffering capability. Since no complementation could be observed among full sized proteins, we evaluated to what extent the superfamily 2 (SF2) helicase core of the smallest DBRH, YfmL, could be functional when hooked to each of the C-terminal end of CshA, CshB, and DeaD/YxiN. None of the different chimeras complemented the different mutants, and instead, all chimeras inhibited the growth of the ΔyfmL mutant, and other combinations were also deleterious. Our findings suggest that the long time divergence between DEAD-box RNA helicase genes has resulted in specialized activities in RNA metabolism and shows that these duplicated genes cannot buffer one another.